2015
DOI: 10.1111/asj.12510
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, carcass traits, physiochemical characteristics and intramuscular fatty acid composition of finishing Japanese black steers fed soybean curd residue and soy sauce cake

Abstract: This study was conducted to determine the effects of dietary soybean curd residue (SCR) and soy sauce cake (SSC) on the growth performance, carcass traits and physiochemical and intramuscular fatty acid (FA) characteristics in Japanese Black steers. Ten steers (29.7 ± 0.3 months old, 856.6 ± 24.4 kg body weight) were assigned to either treatment C, fed a conventional concentrate or T, fed the test diet including dried SCR and SSC for 3 months. In growth performance, dry matter (DM) intake and average daily gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The crude protein content of fresh SSB in the present experiment was slightly above 30% DM Available at www.veterinaryworld.org/Vol.13/May-2020/16.pdf . This value was comparable to that reported in the study of Uddin et al [23] and higher than that of Yasuda et al [24] who reported CP values of 31.0% and 26.6% DM for SSB, respectively. In general, the ensiling treatments with different additives did not alter the nutrient contents of the SSB.…”
Section: Nutrient Composition and Fermentation Characteristics Of Ensiled Ssbsupporting
confidence: 86%
“…The crude protein content of fresh SSB in the present experiment was slightly above 30% DM Available at www.veterinaryworld.org/Vol.13/May-2020/16.pdf . This value was comparable to that reported in the study of Uddin et al [23] and higher than that of Yasuda et al [24] who reported CP values of 31.0% and 26.6% DM for SSB, respectively. In general, the ensiling treatments with different additives did not alter the nutrient contents of the SSB.…”
Section: Nutrient Composition and Fermentation Characteristics Of Ensiled Ssbsupporting
confidence: 86%
“…For example, Kim et al (2012) observed that Hanwoo steers fed diets containing 25 and 35% okara showed higher DM intake (7.99 and 8.11 kg/day, respectively), carcass weight and crude fat content of meat than those fed diets without okara (7.71 kg/d); however, it did not increase the quality grade of the meat. Yasuda et al (2016) assessed the feeding effect of dietary okara on the beef quality of Japanese black steer, and they found that those fed with diet containing okara (15.7%) and soy sauce cake (5.2%) did not show any adverse effect on the growth performance, ruminal fermentation, carcass traits and fatty acid composition in meat (except for C16:1). However, in their study, steers fed okara showed higher total cholesterol and phospholipid contents in blood than those fed nonokara based diet, whereas, in physiochemical characteristics, meat samples from steers fed okara showed lower redness color of beef (a*) and chroma values than those from nonokara based diet.…”
Section: Animal Performancesmentioning
confidence: 99%
“…The effects of the diets may vary depending on the bovine breed [23]. Key fatty acid metabolism-associated genes with upstream regulators (SREBF1) are related to a higher FA index in beef [24].…”
Section: Introductionmentioning
confidence: 99%